RESEARCH AND DEVELOPMENT EXPENDITURES AND FIRM VALUE OF SELECTED INDUSTRIAL GOODS COMPANIES IN NIGERIA - Anidebe, Favour C; Umenzekwe, Peace C; Uchegbu, Callista U. (Journal of Contemporary Issues in Accounting, 2021)
This study examined the effect of research and development expenditures on firm value of industrial goods companies listed on the floor of the Nigerian Stock Exchange over a tenyear period that spanned from 2010 to 2019. The study specifically determined the effect of research and development expenditures on Tobin’s Q, earnings per share, market price per share of selected quoted industrial goods in Nigeria. Ex-post facto research design was adopted and the study population consists of all twelve industrial goods companies listed on the floor of the Nigerian Stock Exchange as at 31st December, 2020, however seven companies were purposively selected on the basis of availability of data. Data was sourced from the annual reports and accounts of the selected companies and the descriptive (mean, maximum, minimum values and standard deviation) and inferential (multiple regression) statistical techniques were employed in analyzing the data. The regression results revealed that research and development expenditures do not significantly affect firm value. Hence, it was concluded that, though research and development expenditures insignificantly contribute to firm value, however effective investments in research and development would help in the improvement of existing products, creation of new products and innovation of the production processes of industrial goods companies thereby improving firm value. Based on the findings, the study therefore recommended among others that innovation be encouraged among firms most especially high technology firms such as industrial goods companies in order to increase their core competitiveness, thus giving it a competitive advantage over other firms.